Potrzeby ewidencyjne systemu motywacyjnego przedstawicieli handlowych - Lew, Grzegorz (Record Needs of Sales Representatives' Motivation System, 2007)
The article presents the connections of the bookkeeping records with the motivation system of the sales representatives in enterprises. The motivation system in controlling is very often a feedback, die system which frequently connects different budgeting elements. In order it could work properly the enterprises need to have an access to all necessary information. This information can be obtained with the help of financial accountancy.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1174, s. 355-361